2003
DOI: 10.1210/en.2003-0096
|View full text |Cite
|
Sign up to set email alerts
|

Ovine Placental Lactogen-Induced Heterodimerization of Ovine Growth Hormone and Prolactin Receptors in Living Cells Is Demonstrated by Fluorescence Resonance Energy Transfer Microscopy and Leads to Prolonged Phosphorylation of Signal Transducer and Activator of Transcription (STAT)1 and STAT3

Abstract: HEK-293T cells transiently transfected with ovine (o) GH receptor (GHR) and prolactin receptor (PRLR) constructs respectively tagged downstream with cyan or yellow fluorescent proteins were used to study ovine placental lactogen (oPL)-stimulated heterodimerization by fluorescence resonance energy transfer (FRET) microscopy. The oPL-stimulated transient heterodimerization of GHR and PRLR had a peak occurring 2.5-3 min after oPL application, whereas oGH or oPRL had no effect at all. The results indicate none or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
2

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(25 citation statements)
references
References 38 publications
0
23
2
Order By: Relevance
“…Most other mammalian groups, including pig, rabbit and dog, do not appear to have such a cluster (Talamantes et al 1980, Forsyth & Wallis 2002, and in the case of dog this was confirmed by a BLAST search of the genome sequence. Placental lactogens appear to use the PRLR signaling pathway (Golos et al 1993, Soares et al 1998, Herman et al 2000, Biener et al 2003 like pituitary PRL. This might suggest that the episodic evolution observed for the PRLR reflects adaptation to the presence of multiple ligands.…”
Section: Biological Significance Of Episodic Evolution Of Prlr and Itmentioning
confidence: 99%
“…Most other mammalian groups, including pig, rabbit and dog, do not appear to have such a cluster (Talamantes et al 1980, Forsyth & Wallis 2002, and in the case of dog this was confirmed by a BLAST search of the genome sequence. Placental lactogens appear to use the PRLR signaling pathway (Golos et al 1993, Soares et al 1998, Herman et al 2000, Biener et al 2003 like pituitary PRL. This might suggest that the episodic evolution observed for the PRLR reflects adaptation to the presence of multiple ligands.…”
Section: Biological Significance Of Episodic Evolution Of Prlr and Itmentioning
confidence: 99%
“…Therefore, an analysis of the ratios of the various potential dimers may be needed to generate a more complete understanding of PRLR signaling. Techniques such as BRET and FRET have been used to examine PRLR dimer formation [14][15][16][17]. However, these techniques collectively constrain the user to cells that express tagged constructs and prevent analysis of tissue samples.…”
Section: Discussion and Further Researchmentioning
confidence: 99%
“…It is now established that ruminant PLs have the ability to bind both PRL-R and GH receptor (GH-R) (Herman et al 2000). Several studies provide evidence that a transient homodimerization of PRL-R occurs in response to ruminant PL (Gertler et al 1996, Sakal et al 1997 and, more recently, the functional heterodimerization of PRL-R and GH-R by PL has been demonstrated in vitro (Herman et al 2000, Biener et al 2003 and in the ovine endometrium (Noel et al 2003). Although it has been established that GH-R was expressed throughout pregnancy in the endometrium (Lacroix et al 1999), no precise quantitative study has been reported for GH-R mRNA expression during the peri-implantation period.…”
Section: Discussionmentioning
confidence: 99%